Composite phenolic resin-based carbon molecular sieve membranes for gas separation - Marta C. Campo (2011)
Composite carbon molecular sieve membranes (c-CMSM) were prepared from phenolicresin loaded with boehmite by a single dippingdryingpyrolysis step. The composite membranewas analyzed by scanning electron microscopy, high resolution transmission electronmicroscopy, X-ray diffraction, thermogravimetric analysis, mercury porosimetry, CO2adsorption and permeation experiments. It was produced a 2 lm thick composite uniformlayer on top of a a-Al2O3 support. The composite top layer exhibited nanowires of Al2O3 12 nm thick and 1030 nm long well dispersed in a microporous carbon matrix. The microporesnetwork accounted for 63% of the total pore volume (DR isotherm). The c-CMSM exhibitedideal O2/N2 and C3H6/C3H8 permselectivities of 5 and 15, respectively. The performanceof the c-CMSM for pair C3H6/C3H8 was above the upper bound curve for polymeric membranes,making it a promising vehicle for olefin purification.